Pharmacokinetic and Biodistribution Analysis of 5-Fluorouracil- and Celecoxib-loaded Eudragit S100-coated Chitosan Microspheres Intended for Colon-specific Delivery - Bansal, Vikas (Asian Journal of Pharmaceutics (AJP), 2019)
Background and Objectives: Colon cancer is one of the leading causes of deaths around the world in human beings. In the present investigation, pharmacokinetic and biodistribution analysis of eudragit-coated chitosan microspheres bearing 5-fluorouracil (5-FU) and celecoxib (Cb) combination (5-FU-Cb-Ch-ES-MSs) was carried out in Wistar rats. Materials and Methods: The tailored microspheres and a suspension of 5-FU and Cb (5-FU-Cb-PS) at the dose of 15 mg/kg of 5-FU and 3.3 mg/kg of Cb, respectively, were administered through oral route of administration. Results and Discussion: 5-FU-Cb-PS exhibited Cmax of 36.71 ± 3.23 μg/ml at tmax of 1 ± 0.17 h for 5-FU. On the other hand, Cmax of 10.14 ± 1.16 μg/ml at tmax of 10.26 ± 0.58 h was noticed for 5-FU released from 5-FU-Cb-Ch-ES-MSs. 5-FU-Cb-PS showed Cmax of 22.48 ± 5.32 μg/ml at tmax of 8 ± 0.00 h for Cb. Correspondingly, Cmax of 3.18 ± 0.16 μg/ml at tmax of 12.39 ± 0.62 h was observed for Cb released from 5-FU-Cb-Ch-ES-MSs. Moreover, at the end of 8 h, 5-FU-Cb-Ch-ES-MSs delivered a substantial amount of 5-FU (56.3 μg/g) and Cb (78.6 μg/g) in the colon, the site of action. Conclusion: This remarkable therapeutic concentration of both the drugs in the colon may be associated with pH-dependent solubility of eudragit S100 and subsequent degradation of Ch core in the colonic milieu due to the presence of polysacharidase enzyme. Therefore, it can be postulated that the 5-FU-Cb-Ch-ES-MSs is a potential candidate for further in vivo study.